Structural elucidation of tungsten compounds containing arylamine, piperazine and morpholine fragments of pyrrole and keto-amine ligands. (24th November 2015) - Chen, Guan-Xuan; Datta, Amitabha; Hsiao, Hung-Chang; Lin, Chia-Her; Huang, Jui-Hsien
Graphical abstract: Various imido tungsten derivatives incorporating bi-dentate pyrrole–piperazine, pyrrole–morpholine, pyrrole–imine and keto-amine precursors were synthesized and characterized by 1 H and 13 C NMR spectroscopy and single crystal X-ray diffraction analysis. Abstract: Various imido tungsten derivatives incorporating bidentate pyrrole–piperazine, pyrrole–morpholine, pyrrole–imine and keto-amine precursors were synthesized. Reacting W(N t Bu)2 (NH t Bu)2 with one equivalent of the pyrrole–phenylpiperazine ligand C4 H3 NH-[2-CH2 N(CH2 CH2 )2 NPh] in toluene generated [W(N t Bu)2 (NH t Bu)C4 H3 N-[2-CH2 N(CH2 CH2 )2 NPh]] (1 ). Similarly, addition of W(N t Bu)2 (NH t Bu)2 to one equivalent of the pyrrole–morpholine ligand C4 H3 NH-[2-CH2 N(CH2 CH2 )2 O] in toluene afforded [W(N t Bu)2 (NH t Bu)C4 H3 N-[2-CH2 N(CH2 CH2 )2 O]] (2 ), which was converted to [W(N t Bu)2 C4 H3 N-[2-CH2 N(CH2 CH2 )2 O]]2 (μ2 -O) (3 ) in moisture. Reacting the pyrrole–imine ligand C4 H3 NH-[2-CHN(C6 H3 -2, 6- i Pr2 )] with one equivalent of W(N t Bu)2 (NH t Bu)2 in toluene gave [W(N t Bu)2 (NH t Bu)C4 H3 N-[2-CHN(C6 H3 -2, 6- i Pr2 )]] (4 ), which was transformed to [W(N t Bu)(NH t Bu)C4 H3 N-[2-CHN(C6 H3 -2, 6- i Pr2 )](μ-O)]2 (5 ) upon absorbing moisture. Furthermore, when one equivalent of C4 H3 NH-[2-CHNC2 H4 N(C2 H4 )2 O] reacted with W(N t Bu)2 (NH t Bu)2 in toluene, W(N t Bu)2 C4 H3 N-[2-CHNC2 H4 N(C2 H4 )2 O]2 (6 ) was isolated. The tungsten keto-amine compounds W(N t Bu)2 [OCMeCHCMeN(C6 H3 -2, 6- i Pr2 )]2 (7 ) and W(N t Bu)2 [OCMeCHCMeNCH2 CH2 N(CH2 CH2 )2 O]2 (8 ) were obtained by the reaction between W(N t Bu)2 (NH t Bu)2 and two equivalents of the corresponding keto-amine ligands in toluene. All the tungsten derivatives were characterized by 1 H and 13 C NMR spectroscopy. Single crystal X-ray diffraction analysis revealed that in compounds, 1, 3, 5, 6 and7, the central W atom belonged to either a distorted trigonal bipyramidal or an octahedral geometrical arrangement. Overall, the influence of the substituted pyrrole and keto-amine bidentate precursors on the imido tungsten derivatives were explored and structurally constructed.